THE DEVELOPMENT OF SIMILAR DAY LOAD FORECASTING (SDLF) FOR SYSTEM OPERATIONS, TRANSMISSION DIVISION, TENAGA NASIONAL BHD. (TNB) - Ali Kamal Sabri Abdul Aziz, author; Azri Azmi, supervisor; Tajul Ariffin Sulaiman, supervisor; Fakulti Sains Komputer dan Sistem Maklumat (Kuala Lumpur : Universiti Teknologi Malaysia, 2006)
Thesis